(untitled) (CAHIERS MAGELLANES-NS, 2024)
Sustainable practices in e-commerce have emerged as a critical area of focus amid global efforts to mitigate environmental impact. This paper explores the challenges and opportunities inherent in integrating sustainability into digital commerce. Challenges include the carbon footprint of logistics and transportation, packaging waste, energy consumption, consumer behavior, and supply chain transparency. However, opportunities abound, such as adopting green logistics, promoting circular economy initiatives, investing in renewable energy, educating consumers, leveraging data for sustainability, and advocating for regulatory compliance. By addressing these challenges and seizing these opportunities, e-commerce businesses can enhance their environmental stewardship, strengthen brand reputation, and meet the growing demand for sustainable products and practices.